(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the socio-economic aspects of the higher education system. Education creates a flow of benefits not only for individuals, but for society as a whole. The state is interested in raising the educational, scientific and cultural level of society and should contribute to the preservation and improvement of the intellectual potential of the country. High-quality education is an integral mechanism in ensuring the progressive growth of the economy of each state. The market of educational services is specific and insufficiently studied, especially in crisis situations. In this regard, the author analyzed the current state of this market, the current problems of the organization and functioning of the educational services market.